PEMANFAATAN CHINESE KNOT (中国结) SEBAGAI MEDIA EDUKASI BUDAYA TIONGHOA DI SMA KHADIJAH SURABAYA - Rabbani, Dzun Nun Septin Renda; Amri, Miftachul; Adhimas, Yogi Bagus; Qorie, Tiffany; Syafiyah, Nabillah Hanan; Laode, Astianti; Ren, Huiling; Hu, Yifan (Universitas Negeri Surabaya, 2025)
This Community Service Program (PKM) addresses the limited understanding of Chinese culture among high school students, particularly at SMA Khadijah Surabaya. Although interest in learning Mandarin has continued to increase, cultural aspects often receive insufficient emphasis in the curriculum. This makes practical cultural exposure an important yet under-implemented strategy. The primary objective of this program is to provide students with direct cross-cultural learning experiences through a training workshop on crafting Chinese Knot (中国结), a traditional Chinese art form rich in philosophical meanings. The implementation method employed a participatory approach involving live demonstrations, group practice, and cultural reflection, supported by comprehensive documentation and reporting. Data analysis was conducted qualitatively through observation, interviews, and evaluation of students’ final craft products. The results indicate an enhanced student understanding of Chinese cultural values and increased enthusiasm in exploring traditional art through hands-on activities. The main outputs include a video documentary, media coverage, and a nationally published scientific article, all of which contribute to the dissemination and sustainability of the program. In conclusion, the training not only enriches students’ cultural competence but also reinforces the relevance of Mandarin language learning within its authentic cultural context, positively contributing to character development and multicultural awareness.